2004
DOI: 10.1185/030079904x17956
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of omega-3 fatty acids in secondary prevention post-myocardial infarction

Abstract: The conclusion reached is that omega-3 fatty acids play a significant role in secondary prevention post-myocardial infarction. The mechanisms through which two of these omega-3 fatty acids, eicosapentaenoic acid and docosahexanoic acid, exert their action appear to be distinct and adjuvant to the available standard secondary prevention therapies. The role to be played by the administration of a newly licensed 90% concentrate EPA + DHA formulation (1 g/day capsule: Omacor) is explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…These effects were proven in numerous studies [3,[5][6][7][8][9][10][11]. Antithrombotic effects [1,12,13] and antihypertensive effects [14,15] have also been reported.…”
Section: Introductionmentioning
confidence: 92%
“…These effects were proven in numerous studies [3,[5][6][7][8][9][10][11]. Antithrombotic effects [1,12,13] and antihypertensive effects [14,15] have also been reported.…”
Section: Introductionmentioning
confidence: 92%
“…reduced the risk of sudden cardiac death by 45% and the overall mortality by 20% (Marchioli et al, 2002) and that doses of up to 4 g day À1 doses can be tolerated (reviewed in Harrison and Abhyankar, 2005). Therefore we propose that there is particular scope for the use of dietary DHA and EPA not only to effect proliferation but also in the anti-metastatic treatment of CaP.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are concerns after observations that COX-2 inhibitors increase the risk of cardiovascular events during both the VIGOR and APC trials (reviewed in Krotz et al, 2005;Luo et al, 2005). Unlike the synthetic COX-2 inhibitors, EPA and DHA are associated with a reduced risk of cardiovascular disease and sudden cardiac death (Holub and Holub, 2004;Harrison and Abhyankar, 2005). Trials have shown that the early administration of 1 g day À1 o-3 PUFA supplements , with or without 10 mM AA.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Several mechanisms have been proposed by which FO reduces cardiovascular events, including triglyceride-lowering effects, antiinflammatory effects, antithrombotic effects, and antiarrhythmic effects. 5,6 …”
mentioning
confidence: 99%